Expression of the mouse p53 cellular tumor antigen in monkey cells. - Pinhasi, O (1984)
DNA specific for the murine p53 cellular tumor antigen was linked to the early simian virus 40 promoter and introduced into monkey COS cells either by transfection with recombinant plasmids or by infection with virus. Recipient cells made substantial amounts of a protein apparently identical to mouse p53. Severalfold-larger quantities were detected when cells were transfected with an intron-containing p53-specific segment, as compared with transfection with intronless cDNA. The p53 encoded by the recombinant DNA was capable of complexing with the simian virus 40 T antigen. Transfected p53 was also probably associated with a cellular 68-kilodalton protein, which may be related to a protein coprecipitating with p53 in some transformed cells. These findings confirm the predicted reading frame and protein boundaries and demonstrate that apparently functional p53 can be produced in cells via experimentally introduced recombinant DNA.